Bentonite - Clay - supported cuprous iodide nanoparticles (BENT- CuI NPs): a new heterogeneous catalyst in diversity - oriented synthesis of 1, 2, 3-triazoles in aqueous medium - Chavan, V, Pramod; Charate, Shrinivas P.; Desai, V, Uday; Rode, V, Chandrashekhar; Wadgaonkar, Prakash P. (Chemistryselect, 2019)
Bentonite clay supported cuprous iodide nanoparticles (BENT-CuI NPs) were prepared and demonstrated for the first time as an efficient heterogeneous catalyst in diversity oriented, green synthesis of 1,2,3-triazoles by one-pot, three component reaction between alkyl halides, arylboronic acids, or epoxides with alkynes and sodium azide in aqueous medium. The catalyst was characterized by Inductively Coupled Plasma Atomic Emission Spectroscopy (ICP-AES), Energy Dispersive X-ray Spectroscopy(EDS), Scanning Electron Microscopy (SEM), X-Ray Powder Diffraction (XRD), Transmission Electron Microscopy (TEM) as well as Brunauer-Emmett-Teller (BET) techniques and was found to be reusable for five consecutive runs without significant loss of activity.
Keywords: 1; 2; 3-triazoles; arylboronic acids; click synthesis; epoxides; green chemistry; heterogeneous catalyst